Characteristics of COVID-19 Clinical Trials in China Based on the Registration Data on ChiCTR and ClinicalTrials.gov - Huang, Jihan (Drug Des Devel Ther, 2020)
OBJECTIVE: This study aimed to evaluate the fundamental characteristics of coronavirus disease (COVID-19) clinical trials registered in China. METHODS: COVID-19 clinical trials registered in China were analyzed from databases on ChiCTR and ClinicalTrials.gov. The study designs, samples, primary end points, and intervention measures were evaluated. RESULTS: In total, 262 intervention clinical trials were retrieved on March 10, 2020. Overall, 181 (69.1%) trials involved two groups, 200 (76.3%) trials were randomized parallel trials, 24 (9.2%) trials were double blind, and 60.3% of trials included ≤100 participants. Sixty (22.9%) trials considered symptom improvement as the primary endpoint and 43 (16.4%) trials considered the rate or time at which the subjects became virus-free as the primary endpoint. Of 262 intervention studies, chemical drugs and biological products were studied in 105 (40.1%) intervention studies, of which antiviral drugs accounted for 15.3% and malaria drugs accounted for 8.4% of the studies. Among all trials, 27.9% of the studies used traditional Chinese medicine (TCM), 10.3% used cell therapy, and 5.0% used plasma therapy. CONCLUSION: This study is the first snapshot of the landscape of COVID-19 clinical trials registered in China and provided the basic features of clinical trial designs for the treatment and prevention of COVID-19 to offer useful information to guide future clinical trials on COVID-19 in other countries.